The Impact of Digital Transformation on Cybersecurity in Poland, Slovakia, and Ukraine - Bierecki, Dominik; Karpiuk, Mirosław; Kelemen, Martin; Prylipko, Sergii (PRAWO i WIĘŹ, 2025)
Digital transformation is becoming increasingly widespread, and it can be said that it is an inevitable process. Digitization has enabled the streamlining of a wide range of tasks, from simple everyday activities to complex operations, enhancing efficiency, speed, and cost-effectiveness in their execution. The degree of digitization in a country is a key indicator of its level of development and the competitiveness of its economy. However, the phenomenon of digitization necessitates a heightened focus on cybersecurity measures. Investment in solutions that guarantee cybersecurity is essential for the success of digital transformation, as new technologies are integral to such transformations and will be effectively exploited by cybercriminals and cyberterrorists if not protected. IT systems used in strategic sectors responsible for national or international security must be adequately protected (cybersecurity). Such systems must be resistant to cyberthreats.